A Cyclic Disulfide Diastereomer From Bioactive Fraction of Bruguiera gymnorhiza Shows Anti–Pseudomonas aeruginosa Activity - Dahibhate, Nilesh Lakshman; Shukla, Sanjeev K.; Kumar, Kundan (Frontiers in Pharmacology, 2022)
Pseudomonas aeruginosa is an opportunistic pathogen that commonly causes hospital-acquired infection and is of great concern in immunocompromised patients. The quorum sensing (QS) mechanism of P. aeruginosa is well studied and known to be responsible for pathogenicity and virulence. The QS inhibitor derived from the natural product can be an important therapeutic agent for pathogen control. The present study reports Bruguiera gymnorhiza purified fraction (BG138) role in inhibiting virulence factor production, biofilms formation, quorum sensing molecules, and expression of QS-related genes of P. aeruginosa. Structural characterization of BG138 by high resolution mass spectrometry, fourier transform infrared spectroscopy, 1-D (1H and 13C NMR), and 2-D NMR reveals that fraction is a mixture of already known cyclic disulfide diastereomer namely, brugierol and isobrugierol. The minimum inhibitory concentration (MIC) of BG138 against P. aeruginosa was 32 µg/mL. Biofilm formation was significantly reduced at sub-MIC concentration of BG138. Scanning electron microscopy analysis reports the concentration dependent biofilm inhibition and morphological changes of P. aeruginosa. Flow cytometry based cell viability assay showed that P. aeruginosa cells exhibit increased propidium iodide uptake on treatment with 32 and 64 µg/mL of BG138. At sub-MIC concentrations, BG138 exhibited significant inhibition of virulence factors and reduced swimming and swarming motility of P. aeruginosa. Furthermore, the effect of BG138 on the expression of QS-related genes was investigated by qRT-PCR. Taken together, our study reports the isolation and structural characterization of bioactive fraction BG138 from B. gymnorhiza and its anti-biofilm, anti-virulence, anti-quorum sensing and cell-damaging activities against P. aeruginosa.